Characterization of TEM1/endosialin in human and murine brain tumors - Carson-Walter, Eleanor B (BioMed Central, 2009)
BACKGROUND: TEM1/endosialin is an emerging microvascular marker of tumor angiogenesis. We characterized the expression pattern of TEM1/endosialin in astrocytic and metastatic brain tumors and investigated its role as a therapeutic target in human endothelial cells and mouse xenograft models. METHODS: In situ hybridization (ISH), immunohistochemistry (IH) and immunofluorescence (IF) were used to localize TEM1/endosialin expression in grade II-IV astrocytomas and metastatic brain tumors on tissue microarrays. Changes in TEM1/endosialin expression in response to pro-angiogenic conditions were assessed in human endothelial cells grown in vitro. Intracranial U87MG glioblastoma (GBM) xenografts were analyzed in nude TEM1/endosialin knockout (KO) and wildtype (WT) mice. RESULTS: TEM1/endosialin was upregulated in primary and metastatic human brain tumors, where it localized primarily to the tumor vasculature and a subset of tumor stromal cells. Analysis of 275 arrayed grade II-IV astrocytomas demonstrated TEM1/endosialin expression in 79% of tumors. Robust TEM1/endosialin expression occurred in 31% of glioblastomas (grade IV astroctyomas). TEM1/endosialin expression was inversely correlated with patient age. TEM1/endosialin showed limited co-localization with CD31, αSMA and fibronectin in clinical specimens. In vitro, TEM1/endosialin was upregulated in human endothelial cells cultured in matrigel. Vascular Tem1/endosialin was induced in intracranial U87MG GBM xenografts grown in mice. Tem1/endosialin KO vs WT mice demonstrated equivalent survival and tumor growth when implanted with intracranial GBM xenografts, although Tem1/endosialin KO tumors were significantly more vascular than the WT counterparts. CONCLUSION: TEM1/endosialin was induced in the vasculature of high-grade brain tumors where its expression was inversely correlated with patient age. Although lack of TEM1/endosialin did not suppress growth of intracranial GBM xenografts, it did increase tumor vascularity. The cellular localization of TEM1/endosialin and its expression profile in primary and metastatic brain tumors support efforts to therapeutically target this protein, potentially via antibody mediated drug delivery strategies.